2017
DOI: 10.1007/s13770-016-0004-3
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogen (Daidzein) Promotes Chondrogenic Phenotype of Human Chondrocytes in 2D and 3D Culture Systems

Abstract: Clinical investigations have shown a significant relationship between osteoarthritis (OA) and estrogens levels in menopausal women. Therefore, treatment with exogenous estrogens has been shown to decrease the risk of OA. However, the effect estrogen has not been clearly demonstrated in the chondrocytes using phytoestrogens, which lack the specific side-effects of estrogens, may provide an alternative therapy. This study was designed to examine the possible effects of phytoestrogen (daidzein) on human chondrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Similarly, another phytoestrogen, daidzein, had anti-inflammatory and anti-oxidant effects in a rat OA model, especially when in combination with hyaluronic acid therapy [ 201 ]. In human chondrocytes, daidzein has had comparable results, having positive effects on ECM formation and pheotype regulation [ 202 ]. These studies demonstrate using phytoestrogen as a therapy method could be a promising approach to treat OA.…”
Section: Regeneration and Preventionmentioning
confidence: 99%
“…Similarly, another phytoestrogen, daidzein, had anti-inflammatory and anti-oxidant effects in a rat OA model, especially when in combination with hyaluronic acid therapy [ 201 ]. In human chondrocytes, daidzein has had comparable results, having positive effects on ECM formation and pheotype regulation [ 202 ]. These studies demonstrate using phytoestrogen as a therapy method could be a promising approach to treat OA.…”
Section: Regeneration and Preventionmentioning
confidence: 99%
“…Even though it has been proven that those acids promote differentiation into bone cells (1518), their capacity to generate, on their own, a morphologic differentiation into cartilage cells is a topic of debate (19,20). However, when those acids are combined with other co-factors, they aid in the process of differentiation into chondrocytes (14,2123). According to previous reports of in vitro trials on animal models and human patients (11,24), the combination of the compounds present in BIOF2 act in synergy to modify the intra-articular microenvironment and stimulate articular regeneration by producing molecular and morphologic alterations in synovial fluid cells and chondrocytes (11).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between phytoestrogens and osteoarthritis is currently less studied and the relationship between phytoestrogens and OA is not consistent across studies. the study of Shen CL et al concluded that genistein, among others, can be anti-arthritic, and Mahmod et al [35] found in an experimental study based on human chondrocytes that the phytoestrogen daidzein had a signi cant effect on the maintenance of human chondrocyte phenotype and extracellular matrix formation, Gundogdu et al [36] concluded that the phytoestrogen daidzein has anti-in ammatory and antioxidant effects in a rat model of OA, and Jia C et al found in an experimental study based on human articular cartilage that the phytoestrogen formononetin inhibited the induction of nuclear factor κB and AKT by IL-1β. κB and AKT activation and thus could be used as a potential drug for OA treatment [37].…”
Section: Discussionmentioning
confidence: 98%